An Overview of Biodegradable Polymers: Revolutionizing Biomedical Applications by Increasing Stability and Biocompatibility for Biomaterial Applications from Lumen-Apposing Metal Stents to Dental Implants - Mehdi Karimi; Azadeh Asefnejad; Bahareh Noshadi; Foad Iranmanesh; Peiman Nasri (Nanochemistry Research, 2025)
The utilization of biodegradable polymers is crucial for advancing biomedical applications, particularly in the production of scaffolds for tissue engineering and implants. These polymers offer non-toxicity, biocompatibility, and biodegradability, making them ideal for enhancing the stability and functionality of biomaterials. Unlike traditional metal implants, tissue engineering relies on porous biodegradable materials that support cellular activities and integrate with surrounding tissues through natural degradation processes. The development of biodegradable polymers with specific physical properties—such as plasticity, mechanical strength, porosity, and bioactivity—is essential for the success of these scaffolds. This approach fosters cellular growth and establishes an optimal interface, facilitating natural tissue regeneration. While significant progress has been made, challenges remain, particularly regarding biomicroscopic evaluations of these materials. This overview not only highlights the most common biodegradable polymers but also emphasizes their applications in various biomedical contexts, including lumen-apposing metal stents and dental implants, along with the in-vivo degradation processes of the scaffolds. Understanding the biochemical characteristics of these materials is vital for promoting the targeted recruitment of cells to the implantation site.